Robust adaptive fault-tolerant control for a class of uncertain nonlinear systems with multiple time delays. (May 2016) - Wu, Li-Bing; Yang, Guang-Hong
Abstract : Highlights: The robust adaptive fault accommodation scheme is developed to stabilize a class of MISO nonlinear systems with multiple time delays, which include both in normal and faulty cases. By using fuzzy logic system (FLS) to approximate the desired nonlinear function, a novel adaptive fuzzy fault-tolerant control algorithm is designed to compensate the effects of mismatching parameter uncertainty, external disturbance, multiple time delays perturbation and actuator failures. It is proved that the design condition of the direct adaptive fault-tolerant controller proposed in this paper has much wider scope of the applicability than the existing schemes. Simulation results of a two stage chemical reactor system with delayed recycle streams demonstrate the effectiveness and advantages of the presented control method. Abstract: This study is concerned with the problem of robust adaptive fuzzy fault-tolerant control for a class of uncertain nonlinear systems with mismatching parameter uncertainties, external disturbances, multiple state time delays perturbations and actuator failures, which include loss of effectiveness, outage and stuck modes. A novel direct adaptive fuzzy tracking control scheme is developed to achieve the fault-tolerant control objective. First, by introducing a positive nonlinear control gain function, the effects of state time delays and actuator failures are effectively compensated. Then, a suitable fuzzy logic system (FLS), which is used to approximate the corresponding nonlinear function, is constructed to eliminate the influences on mismatched parameter uncertainty and external disturbance. Moreover, it is shown that all the closed-loop system signals are uniformly bounded and that the tracking error converges to a small neighborhood of the origin via Lyapunov–Krasovskii stability analysis. Finally, the proposed adaptive fuzzy fault-tolerant tracking design approach is illustrated on a two stage chemical reactor system with delayed recycle streams.